ON SURFACE FRACTURE OF RAIL HEADS - Datsyshyn, O. P.; Marchenko, H. P.; Glazov, A. Y. (Science and Transport Progress, 2017)
Purpose. The formation of crack-like defects in rails of railway tracks is a serious problem for engineering practice because of the danger of creating emergency situations. The purpose of this work is to establish theoretically the characteristic angle of propagation of surface cracks in the rail heads of railway rails, which is basic in the formation of typical surface contact fatigue damages, such as pitting, «checks» and «squat». It is also necessary to find the conditions for determining this angle. Methodology. The investigations were carried out on the basis of the method of singular integral equations. The rail damaged by the surface crack was modeled with a half-plane with an edge cut, and the action of the wheel on the rail by unidirectional repeated translational movement along the edge of the half-plane of the Hertzian contact forces with the tangential component. The problem of determining the stress intensity factors in the vicinity of the crack tip in the rail head was reduced to a system of two real singular integral equations which were solved numerically by the Gauss-Chebyshev mechanical quadrature method. The complexity of the problem consists in the fact that the boundaries of the contact areas and the opening of the crack faces are unknown beforehand and they change when the model contact forces move. These boundaries were determined simultaneously with solving the integral equations of the problem from additional conditions by the iteration method. Findings. The presence of the characteristic angle of propagation of mode II surface cracks in the rail head has been established theoretically and the conditions for its determination have been put down. The results obtained are in good agreement with engineering and experimental data. Originality. For the first time, the values of the characteristic angle were theoretically determined, under which at the initial stage, the surface contact fatigue cracks propagate in the head of the railway rail under the action of the wheels. Conditions for determining this angle have been also put down. Practical value. The received data are of great importance for engineering practice, since they reveal the nature of surface contact fatigue defects under various operating conditions and allow to predict their contact strength and durability.